2008
DOI: 10.1530/eje-08-0814
|View full text |Cite
|
Sign up to set email alerts
|

The use of GnRH agonists in precocious puberty

Abstract: In this review several aspects of gonadotrophin releasing hormone agonists (GnRHa) treatment in central precocious puberty (CPP) are highlighed. These include issues of the definition of precocity, assessment of CPP and thelarche variants. Indications for treatment with GnRH agonists are discussed, not only in CPP but also in children with other reasons to suppress central activation, e.g. adopted or developmental retardation. Finally, outcome data are summarized, both on growth and psychosocial parameters.Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 38 publications
1
49
0
7
Order By: Relevance
“…Follow-up data examining long-term risks or side effects of puberty blockers used for the purpose of halting a normally occurring rather than precocious puberty in transgender youth have not been published, but extrapolation from follow-up studies of blockers used for precocious puberty show promising results, with no known untoward consequences. 48 The goal of pubertal suppression is to decrease the gonadal secretion of and end-organ effects of endogenous sex steroids. GnRH analogs are administered in the form of intramuscular or subcutaneous injections or subcutaneous implants.…”
Section: Pubertal Suppressionmentioning
confidence: 99%
“…Follow-up data examining long-term risks or side effects of puberty blockers used for the purpose of halting a normally occurring rather than precocious puberty in transgender youth have not been published, but extrapolation from follow-up studies of blockers used for precocious puberty show promising results, with no known untoward consequences. 48 The goal of pubertal suppression is to decrease the gonadal secretion of and end-organ effects of endogenous sex steroids. GnRH analogs are administered in the form of intramuscular or subcutaneous injections or subcutaneous implants.…”
Section: Pubertal Suppressionmentioning
confidence: 99%
“…Çalışmalarda boy kazancı 3-10 cm arasında değişmektedir (6). Olgumuzda da Triptorelin asetat tedavisi 28 günde bir 3.75 mg intramüsküler şekilde verilmiştir (7).…”
Section: Discussionunclassified
“…These ultrastructure findings likely reflect the suppressive effects of leuprorelin on the synthesis of gonadotropins in the markedly stimulated gonadotropes 8 weeks after castration. Although the sustained treatment with GnRH agonists has been conventionally used to prevent the synthesis of gonadal sex steroids which potentially aggravate androgen-or estrogen-dependent diseases such as prostate cancer, endometriosis and uterine myomas (Barbieri 1992, Engel et al, 2007, the findings described above clearly proved the putative efficacy of GnRH agonists on the clinical application for suppressing the excessive secretion state of pituitary gonadotropins in diseases such as central precocious puberty in juveniles (Antoniazzi and Zamboni, 2004;Mul and Hughes, 2008). In summary, our present study demonstrated in detail the ultrastructural changes in the ER and Golgi apparatus of pituitary gonadotropes under the influence of a longacting depot formulation of the GnRH agonist, leuprorelin.…”
Section: Discussionmentioning
confidence: 99%